The influence of age group and match period on tactical performance in youth soccer: A full season study - Moreira Praça, G.; Rochael, M.; Francklin, G., da Silva, T. R., de Andrade, A. G. P. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Recently developed technological approaches using positional data and network analysis were adopted in this study to investigate the existence of drops in tactical performance from the first to the second half of official matches in two different age groups. Fifty outfield players from U-17 (n = 25) and U-20 (n = 25) youth academies were monitored over the 2020 competitive season. Players` positional data were collected by GPS devices, and all matches were recorded for adoption of the Social Network Analysis approach. The individual and collective performances were monitored for both halves of the matches and compared between age group and match period using a mixed two-way ANOVA. Results indicated the absence of drops in collective tactical performance over the halves, although, on the individual scale, players reduced the spatial exploration from the first half to the second half. Older players presented higher density, LPWRatio and lower spatial exploration than younger players. Teams showed stable collective performance within the match, although drops in individual tactical performance were observed and were not age-dependent. Finally, older players tended to present a higher individual and collective performance.